Recent Progresses in the Treatment of Osteoporosis - Li, Shan-Shan; He, Shi-Hao; Xie, Peng-Yu; Li, Wei; Zhang, Xin-Xin; Li, Tian-Fang; Li, Dai-Feng (Frontiers in Pharmacology, 2021)
Osteoporosis (OP) is a chronic bone disease characterized by aberrant microstructure and macrostructure of bone, leading to reduced bone mass and increased risk of fragile fractures. Anti-resorptive drugs, especially, bisphosphonates, are currently the treatment of choice in most developing countries. However, they do have limitations and adverse effects, which, to some extent, helped the development of anabolic drugs such as teriparatide and romosozumab. In patients with high or very high risk for fracture, sequential or combined therapies may be considered with the initial drugs being anabolic agents. Great endeavors have been made to find next generation drugs with maximal efficacy and minimal toxicity, and improved understanding of the role of different signaling pathways and their crosstalk in the pathogenesis of OP may help achieve this goal. Our review focused on recent progress with regards to the drug development by modification of Wnt pathway, while other pathways/molecules were also discussed briefly. In addition, new observations made in recent years in bone biology were summarized and discussed for the treatment of OP.